The outcome of hospitalized patients with community-acquired pneumonia in Hospital Universiti Sains Malaysia - Abdullah, Shaharudin (2006)
Background: Community-acquired pneumonia (CAP) remains an important cause of hospital admission. Studies have shown that the mortality of patients admitted with community-acquired pneumonia is high. The outcomes have been shown to be influenced by various clinical variables at presentation. Applications of these variables as predictor of severity have been shown to improve patients management outcome. The outcome of patients admitted due to CAP has not been studied in Hospital University Science Malaysia (HUSM). The main purpose of this study was to evaluate outcome in patients who required admission due to community acquired pneumonia in HUSM and to determine factors that influenced their poor outcome. Methodology: This was a retrospective cohort study between January 2004 to December 2004. Records of patients with community-acquired pneumonia admitted to HUSM were screened. This study included all patients aged more than 12 years old who met the inclusion criteria. The following information; demographic data, initial clinical findings, laboratory investigations and type of antibiotics regime given were recorded into customized data collection sheet. Variables obtained were examined for association with mortality. Severity prediction criteria were formulated from identified variables that showed significant association with mortality. Results: Records of 155 patients' that met the inclusion criteria were evaluated. The mean age at presentation was 62 ± 17 years. The mortality rate was 19.4%. Variables that significantly influenced the mortality on multivariate analysis at presentation were presence of important co-morbid illnesses (OR 11.13; p = 0.001 ), confusion (OR 18.72; p = 0.001) and hypoxaemia (OR 10.62; p = 0.002). Other factors identified were low diastolic blood pressure and random blood sugar greater than 13 mmol/1 with odds ratio of 1.08 (p=0.002) and 6.37 (p=0.007) respectively. The presence of any three of following variables on admission; presence of comorbid illness, confusion, low diastolic blood pressure of s 60 mmHg, low oxygen saturation and random blood sugar equal or greater than 13 mmol/1 was associated with a 46.3 fold increase in death. The suggested predictive severity rule identified 21 of the 27 patients who died as having severe community acquired pneumonia. The sensitivity of the suggested severity model for predicting death was 0. 70 and specificity of 0.95. The rule had a negative predictive value of 0.93. Conclusion: The mortality from community-acquired pneumonia requiring hospitalization in our centre is high compared to previous studies. We found that certain factors that influenced the outcome of our patients were almost similar with other previous studies. We found that the presences of three of the five variables (comorbid illness, confusion, low diastolic blood pressure, hypoxaemia and hyperglycaemia) would allow us to detect patients who at risk of poor outcome.